An integrative taxonomic study reveals a new species of Tylodelphys Diesing, 1950 (Digenea: Diplostomidae) in central and northern Mexico. Issue 6 (28th October 2015) - García-Varela, M.; Sereno-Uribe, A.L.; Pinacho-Pinacho, C.D.; Hernández-Cruz, E.; Pérez-Ponce de León, G.
Abstract: Tylodelphys aztecae n. sp. (Digenea: Diplostomidae) is described from adult specimens obtained from the intestine of the pied-billed grebe ( Podilymbus podiceps ) and the metacercariae found in the body cavity of freshwater fishes of the families Goodeidae and Cyprinidae in eight localities across central and northern Mexico. The new species is mainly distinguished from the other four described species of Tylodelphys from the Americas ( T. adulta, T. americana, T. elongata and T. brevis ) by having a forebody slightly concave, a larger ventral sucker, two larger pseudosuckers and by having between 2 and 7 eggs in the uterus. Partial DNA sequences of the mitochondrial gene cytochrome c oxidase subunit I ( cox1 ), and the internal transcribed spacers (ITS1+5.8S+ ITS2) of the ribosomal DNA, were generated for both developmental stages and compared with available sequences in GenBank of other congeners. The genetic divergence estimated among Tylodelphys aztecae n. sp. and other congeneric species varied from 12 to 15% for cox1, and from 3 to 11% for ITS. In contrast, the genetic divergence among metacercariae and adults of the new species was very low, ranging between 0 and 1% for cox1 and between 0 and 0.3% for ITS. Phylogenetic analyses inferred with both molecular markers using maximum likelihood and Bayesian inference placed the adults and their metacercariae in a single clade, confirming that both stages are conspecific. The morphological evidence and the genetic divergence, in combination with the reciprocal monophyly in both phylogenetic trees, support the hypothesis that the diplostomids found in the intestines of the pied-billed grebe bird and the body cavity from goodeid and cyprinid fishes in central and northern Mexico represent a new species.